Developing Individual Students through Changes of Thinking Pattern and Self Perception on Learning Activities - Pratiwi Indah Sari; Redi Indra Yudha (STAI Hubbulwathan Duri, 2022)
The purpose of the study was to know the development of students through the changes of thinking patterns and self-perceptions of students during learning process. The design of research was qualitative research. The informant or the most appropriate key person was the 2016 Students of Economic Education Study Program. The research data was collected with observation, interviews and documentations. The research concluded that there was an increase in student understanding positively. This was because, the students were more invited to participate in depth through various case studies given on course materials rather than just observing. Thus, it can be concluded that the learning process that is on the bench of college or college education level was very different from other education level, which in the learning process is put forward the development of insights and deeper patterns of thinking. Nevertheless, there was still a tendency of student minds that had not been directed so that they could be free to create through various opinions that certainly could be accounted for.